Für wen lohnt sich Arbeit? Partizipationsbelastungen im Steuer-, Abgaben- und Transfersystem - Maximilian Blömer; Andreas Peichl (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2020)
In dieser Studie untersuchen wir die Beschäftigungsanreize des deutschen Steuer-, Abgaben- und Transfersystems. Um die Anreizwirkungen von Steuern und Transferleistungen zu beurteilen, stellt man typischerweise die Frage, wie stark ihr verfügbares Einkommen steigt, wenn eine Person das Arbeitsangebot ausweitet. Während die effektive Grenzbelastung ("intensive margin") relevant ist, um die Anreize bei Entscheidungen über kleine Änderungen im Arbeitsangebot zu analysieren, erweitert die Darstellung von Partizipationsbelastungen die Analyse um diskrete Entscheidungen. Diskrete Entscheidungen sind beispielsweise die prinzipielle Aufnahme einer Erwerbstätigkeit oder der Wechsel von einer Teil- zu einer Vollzeitbeschäftigung. Solche Entscheidungen werden als Entscheidungen an der "extensive margin" bezeichnet. Die Partizipationsbelastung gibt an, wie viel Prozent des gesamten individuellen Bruttoeinkommens als Steuern und Abgaben sowie durch Transferentzug einbehalten werden. Die berechneten Partizipationsbelastungen legen also auch offen, wie groß der Lohnabstand ist. [...] – – In this study,we examine indicators for labor supply incentives of theGermantax and transfer system. To assess incentives of taxes and transfer policies, one typically asks how much the disposable household income is increasing when a person expands his or her labor supply. The effective marginal tax rate is relevant to determine the incentives to take decisions about small changes in labor supply (the "intensive margin"). This study additionally includes the display of participation tax rates (PTR) to analyze discrete decisions. Examples for discrete decisions are the general decision of taking up or changing employment from a part-time to a full-time job. Such decisions are referred to as decisions at the "extensive margin". The PTR indicates what percentage of total individual gross income is taxed away and withdrawn due to transfer reduction. The calculated PTR therefore also reveals how large the net wage increase is. In this study, we examine the question which central elements of the tax system, the social security contribution system and which transfer policies determine the level of PTR. We also investigate how the PTR has developed in real terms over time. Different political sides regularly criticize the phenomenon of "bracket creep" in Germany, i.e. the increase in the tax burden over time due to a delayed adjustment of the income tax brackets to the nominal wage growth. We examine this aspect in terms of the overall tax and transfer system. [...]
Additional information: Studie im Auftrag der Bertelsmann Stiftung.
Keywords: 330